Acid functionalized cellulose nanocrystals and its effect on mechanical, thermal, crystallization and surfaces properties of poly (lactic acid) bionanocomposites films: A comprehensive study. (28th September 2016) - Dhar, Prodyut; Bhasney, Siddharth Mohan; Kumar, Amit; Katiyar, Vimal
Abstract: This work reports the fabrication of four varieties of cellulose nanocrystals(CNCs) through hydrolysis with different acids which leads to their tailored physical, structural, thermal and surface characteristics. The hydroxyl groups of CNCs are substituted with anionic-moieties from acid which alters its interfacial interaction with PLA matrix, as predicted from dispersion surface energy and work of adhesion values. Interestingly, tunable aspect ratios of various acid-derived CNCs have substantial effect on mechanical reinforcing-efficiency and thermal behavior of nanocomposites. CNCs with high aspect ratio improved the elastic modulus of nanocomposites whereas with low aspect ratio accelerated the crystallization rate. The different acid-derived CNCs shows heterogeneous nucleation-driven crystallization phenomenon with propagation of PLA spherulites in three dimensions. Lauritzen-Hoffmann parameters shows that growth of PLA crystals are restricted requiring higher activation-energy to initiate nucleation process. Therefore, this study provides an alternative approach of selecting the appropriate acid-hydrolyzed CNCs for fabrication of CNC-reinforced polymeric nanocomposites with desired properties. Graphical abstract: Highlights: Different acid-hydrolyzed CNCs shows tailored physical and surface characteristics. Dispersion of CNCs in PLA matrix could be predicted from surface energy parameters. CNCs with lower aspect ratio accelerated the crystallization rate. CNCs with higher aspect ratio improved mechanical reinforcement effect. CNCs induced heterogeneous nucleation phenomenon with 3-D growth of spherulites.